Analysis of exome data in a UK cohort of 603 patients with syndromic orofacial clefting identifies causal molecular pathways - Wilson, K; Newbury, DF; Kini, U (Oxford University Press, 2023)
Orofacial cleft (OC) is a common congenital anomaly in humans, which has lifelong implications for affected individuals. This disorder can be classified as syndromic or non-syndromic depending on the presence or absence of additional physical or neurodevelopmental abnormalities, respectively. Non-syndromic cleft is often non-familial in nature and has a complex aetiology, whereas syndromic forms tend to be monogenic. Although individual OC-related syndromes have been frequently described in the medical literature, there has not been a comprehensive review across syndromes, thereby leaving a gap in our knowledge, which this paper aims to address. Six hundred and three patients with cleft-related human phenotype ontology terms were identified within the Deciphering Developmental Disorders study. Genes carrying pathogenic/likely pathogenic variants were identified and reviewed enabling a diagnostic yield of 36.5%. In total, 124 candidate genes for syndromic OC were identified, including 34 new genes that should be considered for inclusion in clinical clefting panels. Functional enrichment and gene expression analyses identified three key processes that were significantly overrepresented in syndromic OC gene lists: embryonic morphogenesis, protein stability and chromatin organization. Comparison with non-syndromic OC gene networks led us to propose that chromatin remodelling specifically contributes to the aetiology of syndromic OC. Disease-driven gene discovery is a valid approach to gene identification and curation of gene panels. Through this approach, we have started to unravel common molecular pathways contributing to syndromic orofacial clefting.